2000
DOI: 10.1056/nejm200006013422203
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Study of Growth Hormone Therapy for Crohn's Disease

Abstract: Our preliminary study suggests that growth hormone may be a beneficial treatment for patients with Crohn's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
102
0
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(109 citation statements)
references
References 18 publications
4
102
0
3
Order By: Relevance
“…14 Indeed, a clinical trial in patients with active CD reported that GH therapy decreased the CDAI score and reduced the need for other medications. 24 IBD is frequently complicated by growth failure in children and wasting in adults. [2][3][4] Although IBDassociated malnutrition is considered the main source of these complications, 5 recent evidence in IBD animal models suggests a direct adverse effect of systemic inflammation on the GH/IGF-1 axis.…”
Section: Discussionmentioning
confidence: 99%
“…14 Indeed, a clinical trial in patients with active CD reported that GH therapy decreased the CDAI score and reduced the need for other medications. 24 IBD is frequently complicated by growth failure in children and wasting in adults. [2][3][4] Although IBDassociated malnutrition is considered the main source of these complications, 5 recent evidence in IBD animal models suggests a direct adverse effect of systemic inflammation on the GH/IGF-1 axis.…”
Section: Discussionmentioning
confidence: 99%
“…2,39,40 Here, we have demonstrated that peripheral activation of the mu opioid pathway protects against DSS-induced intestinal injury and enhances wound healing. We have shown that the MORspecific agonist DALDA activates proliferative signaling in the intestine, a response associated with enhanced colonocyte-derived Stat3 activation and induction of cytoprotective genes.…”
Section: Discussionmentioning
confidence: 91%
“…For example, recombinant human growth hormone induced protective effects in TNBS-induced colitis [309]. A preliminary study showed that human growth factor was effective in CD, it improved the clinical symptoms (the number of liquid/soft stools, severity of abdominal pain and overall well being) and a statistically significant increase in circulating levels of IGF-1 was observed [310]. Further, placebo controlled human studies should be performed to determine the real place of growth factor in the therapy of IBD.…”
Section: Growth Hormone (Gh)mentioning
confidence: 99%